(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To understand the context experienced by homeless people, with ostomies, in a municipality in southern Brazil. Method: A qualitative ethnographic study, whose sample consisted of four individuals. Data collection took place from May to June 2022. Participant observation, field diary, data from medical records, and interviews were used. Results: Regarding the participants’ profile, the majority are young adults, male, and drug users. All participants had children and received government assistance. The average duration of living with an ostomy was two years and the primary reason was gunshot wounds. The aim was to understand the characteristics and health conditions of these individuals, viewed within the context of the Brazilian healthcare system and the way services are organized to provide care. Conclusion: It was found that in addition to the vulnerability of being homeless, their life context leads to social and mental consequences, and the invisibility of these individuals within society and the healthcare network is remarkable.